Variation in Word Formation and Lexical Choice: A Stylistic Translation of “Asahan Dalam Angka 2015” Text - Devi Annisa Marpaung; Budi Rizka; Ely Ezir (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
In case of recent global and social changes, academic fields under language and communication pay their interests in various forms of translation, for instance, official text. Translating official text very often meets a gap, that is, inappropriate meanings in the target text. Therefore, the aims of the study are to identify the stylistic approaches that contribute to the translation of the ST into the TT in terms of stylistic qualified translation and to identify the translation accepted by the native speakers of TT. Equivalence in meaning which is a central meaning-focused in the translation work has not been done well by the translator. The farther its equivalence is the farther the gap is. The gap, however, leads to a misunderstanding of the text. Misunderstanding of the text will either spoil the ideas or loosen the information of the source text. Word Formation Variation (WFV) 19 data (14.61 %), and Lexical Choice Variation (LCV) 28 data (21.53%).